Exploring psychological capital as enhancer of instructional coaches’ competencies - Burhanuddin, Nur Aimi Nasuha (2021)
Research evidence suggested that psychological capital (PsyCap) has been increasingly recognized and positively linked with employee’s productivity. It is a critical factor in motivation, effective cognitive processing and achievement, entailing the positive evaluation of a given situation and the drive to succeed (Peterson et al., 2011). The existing evidence however is mostly within industrial and business organisation employee and none, if not little, focus is given towards educational organisation. Thus, in order to explore PsyCap among educators, specifically instructional coaches (IC), and to understand how PsyCap is experienced by IC in their practice of instructional coaching, this study put forward three research questions. They include (1) How do instructional coaches experience PsyCap in their practice of coaching? (2) What are the factors that contribute to the development of instructional coaches’ PsyCap? (3) How does PsyCap help instructional coaches to be competent in their profession? These questions aimed to determine ways, factors that influence, and how PsyCap is able to help instructional coaches enhance their coaching competencies. Phenomenological approach was selected since it was deemed the most appropriate approach for the study of a phenomenon of this nature. Data were gathered from seven instructional coaches from six different District Education Offices (DEO) throughout Malaysia. The participants were selected among those who are KHAS C and DG54 grade instructional coaches through purposive sampling. The data collection method employed was mainly in-depth interview with the participants. Each interview was audio-recorded, transcribed verbatim and analysed. In addition, informal observation was also carried out. The validity and reliability of the research was ensured by following Yardley’s Principle of accessing quality for qualitative research: 1) sensitivity to context, 2) commitment and rigour, 3) transparency and coherence and 4) impact and importance. This includes stating the researcher’s position as well as maintaining audit trail. As additional measure, this study also took the approach of clarifying researcher’s bias, member checking, peer debriefing and thick, rich description of the result. Through the themes emerged, the finding showed ways PsyCap was experienced by the instructional coaches, factors that contributed to the development of their PsyCap and how PsyCap helped enhanced their coaching competencies. Extracted from participants’ own words, PsyCap was experienced by the participants through the sense of responsibility, PsyCap as personal resources and PsyCap and work commitment. The exploration of factors that contributed to the development of participants’ PsyCap has brought about supportive working environment, career background as well as spirituality. Being supplemented with inner psychological resources of PsyCap, the IC was able to enhance their coaching competencies through role modeling, encourage others to flourish and build emotional connection with teachers. The study concluded that PsyCap possessed by the study’s participants were unique to them and have aided them in their practice of instructional coaching. This study contributed to the body of knowledge by suggesting potential positive psychological resources to be included in PsyCap which are spirituality and emotional intelligence. Both of these resources were deemed to be highly significant to the context of Malaysian educators. In addition, this study also highlighted the implication for the instructional coaching practices and policies and future research recommendations towards understanding PsyCap in other groups within educational organisation.